Determinants of Biofuels Production and Consumption, Green Economic Growth and Environmental Degradation in 6 Asia Pacific Countries: A Simultaneous Panel Model Approach - Kurniadi, Anggi Putri; Aimon, Hasdi; Amar, Syamsul (International Journal of Energy Economics and Policy, 2021)
This study aims to fill the gaps in previous research in the form of development studies between production and consumption biofuels, green economic growth and environmental degradation in 6 selected Asia Pacific countries (Australia, China, India, Indonesia, South Korea and Thailand) by considering the determinants during the period 2007-2020. This study used a simultaneous panel model approach. The important findings of this study are grouped into 4 analysis models. First, biofuels consumption, capital formation, labor and foreign direct investment have a positive effect on biofuels production. Second, biofuels production, foreign direct investment, GDP per capita and trade openness have a positive effect on biofuels consumption. Third, biofuels production, biofuels consumption and technological innovation have a positive effect on green economic growth, while militarization has a negative effect. Fourth, biofuels production, biofuels consumption, green economic growth and cleaner energy have a negative effect on environmental degradation, while population and poverty have a positive effect. The development of biofuels oil is aimed at realizing the transition from fossil-based energy to biomass-based energy which is expected to be environmentally friendly and sustainable. Biofuels oil has great potential in supporting renewable energy development to increase green economic growth and reduce environmental degradation. Keywords: Biofuels Production, Biofuels Consumption, Green Economic Growth, Environmental Degradation, Simultaneous Panel Model, Asia Pacific JEL Classification: C33, C51, Q21, Q43 DOI: https://doi.org/10.32479/ijeep.11563